Synthesis of hollow spherical polyaniline by using poly(styrene‐co‐acrylic acid) sphere as the template for high adsorption of Cr(VI). Issue 35 (22nd July 2022) - Chang, Hejia; Meng, Qinghu; Liu, Defa; Wu, Yue; Yang, Zhizhou; Sun, Bin; Liu, Fang; Liu, Yu
Abstract: Synthesis of hollow spherical polyaniline (HSPANI) with the merits of facile strategy, low cost, low safety risk and high adsorption capacity of Cr(VI) is always a big challenge. In this manuscript, we proposed a facile way to preparation of HSPANI by using the poly(styrene‐co‐acrylic acid) sphere as template. The results indicated that HSPANI was emeraldine comprised of lots of basically uniform hollow spheres, and its average pore diameter was about 300 nm. HSPANI displayed high adsorption capacity of Cr(VI), and its value arrived at 601.3, 347.8, 235 mg g −1 at pH = 1, 2, and 3, respectively, which were high than many other adsorbents. The endothermic, spontaneous and chemical adsorption process was responsible for this adsorption. The Cr(VI) adsorption capacity was significant relied on its pH, contact time, Cr(VI) concentration and adsorption temperature. The adsorption behavior was well agreed with pseudo second‐order equation and Redlich–Peterson isotherm models. HSPANI exhibited remarkable selectivity for adsorption of Cr(VI) even if the K +, Cu 2+, NO3 − and SO4 2− were coexisted. HSPANI also displayed excellent regeneration performance. Therefore, this work not only provided a facile way to synthesis of hollow spherical polyaniline, but also supplied a potential adsorbent for adsorption of Cr(VI) from the industrial wastewater. Abstract :